2022
DOI: 10.1038/s41467-022-30257-z
|View full text |Cite
|
Sign up to set email alerts
|

MYC drives aggressive prostate cancer by disrupting transcriptional pause release at androgen receptor targets

Abstract: Abstractc-MYC (MYC) is a major driver of prostate cancer tumorigenesis and progression. Although MYC is overexpressed in both early and metastatic disease and associated with poor survival, its impact on prostate transcriptional reprogramming remains elusive. We demonstrate that MYC overexpression significantly diminishes the androgen receptor (AR) transcriptional program (the set of genes directly targeted by the AR protein) in luminal prostate cells without altering AR expression. Analyses of clinical specim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 76 publications
9
38
0
Order By: Relevance
“…Altogether, our data demonstrated that the combination of EZH2i and BETi is a rational pharmacological strategy to target c-myc in late stage mCRPC cells that are almost unresponsive to both GSK126 and JQ1 when used as a single drug treatment. From a clinical point of view our finding is relevant, considering that divergent AR (low) and MYC (high) transcriptional signatures predisposes patients to fail standard-of-care therapies and progress to the mCRPC stage 52 . Therefore, considering the heterogeneity of late stage mCRPC disease, appropriate patient selection through molecular diagnostics may be necessary to identify the right population that might benefit of the proposed myc-targeting strategy to maximise the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Altogether, our data demonstrated that the combination of EZH2i and BETi is a rational pharmacological strategy to target c-myc in late stage mCRPC cells that are almost unresponsive to both GSK126 and JQ1 when used as a single drug treatment. From a clinical point of view our finding is relevant, considering that divergent AR (low) and MYC (high) transcriptional signatures predisposes patients to fail standard-of-care therapies and progress to the mCRPC stage 52 . Therefore, considering the heterogeneity of late stage mCRPC disease, appropriate patient selection through molecular diagnostics may be necessary to identify the right population that might benefit of the proposed myc-targeting strategy to maximise the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Considering the coordinated action of c-myc and AR in PCa development ( 64 , 65 ), the effect of anti-androgens was evaluated. The results showed an increased expression of p-c-myc with bicalutamide, enzalutamide and apalutamide exposure of LNCaP-WT cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, AR-directed therapies suppress AR activity in patients with metastatic PCa, such that resistant tumors are less dependent on AR for growth and survival [ 39 ]. Thus, histologically and clinically aggressive tumors may reflect a causal link between increased MYC activity and decreased but persistent AR activity, due in part to a transcriptional pause-release effect that accounts for lower AR tumors having worse clinical outcomes [ 4 , 40 ]. A logical future study will be to broadly assess the metabolic and lipogenic ramifications of differential AR/MYC status.…”
Section: Discussionmentioning
confidence: 99%